Preliminary studies to evaluate the use of spectral data in monitoring of apple orchard parameters - Szabó, Andrea; Tamás, János; Nagy, Attila (Acta Agraria Debreceniensis, 2022)
The introduction/application of precision agricultural technologies has more important role in various fruit growing sectors among others apple growing. Remote sensing methods can detect electromagnetic waves where the green colour of the leaf is responsible for the chlorophyll content. The absorption of chlorophyll is in the wavelength range of 450–670 nm. Samples of apple tree leaves were taken on a weekly basis from the apple orchard at Horticultural Unit of Pallag on University of Debrecen in 2019 summer. Our studies were performed on 2 cultivars (Early Gold, Golden Reinders) and the samples were processed using 2 methodologies: a non-destructive spectral method and spectrophotometric method chlorophyll and carotenoid contents were calculated, which were created into some groups and compared with the spectral values. When the plant begins to lose strong green colour and turns yellow spectral measurements show that chlorophyll content decreases as the proportion of chlorophyll-carotenoid in the plant changes.  In case of grouping into intervals, it can be observed that as the chlorophyll content increases the reflectance value decreases continuously due to the strong absorption. Based on the results, close relationship between the pigments can be detected.